A public health approach to gambling regulation: countering powerful influences. (August 2021) - van Schalkwyk, May C I; Petticrew, Mark; Cassidy, Rebecca; Adams, Peter; McKee, Martin; Reynolds, Jennifer; Orford, Jim
Summary: Often portrayed as a harmless leisure activity in the UK, gambling is being increasingly recognised as a public health concern. However, a gambling policy system that explicitly tackles public health concerns and confronts the dependencies and conflicts of interest that undermine the public good is absent in the UK. Although there is a window of opportunity to change the gambling policy system, with the UK Government's launch of a review of the Gambling Act 2005, the adoption of a comprehensive and meaningful public health approach is not guaranteed. Too often, government policy has employed discourses that align more closely with those of the gambling industry than with those of the individuals, families, and communities affected by the harms of gambling. In view of the well described commercial determinants of health and corporate behaviour, an immense effort will be needed to shift the gambling discourse to protect public health. In this Viewpoint, we seek to advance this agenda by identifying elements that need challenging and stimulating debate.